Google, Facebook, And China: Internet Supremacy and Digital Sovereignty - Mubarok, Sofi; Candra, Rudi (Dauliyah: Journal of Islam and International Affairs, 2023)
The relationship between the internet and the state has become a interesting topic lately, especially after the United States' rejection of the Huawei technology company, which allegedly used its technology as a spy in 2019. This paper will dissect this phenomenon using George Orwell's perspective on how to fight against oppressive rulers with the power of information technology and Jack Pinkowski who on the contrary sees the potential for a harmonious relationship between the state and information technology that will be able to create a balance of power between society and the state. Using books, scientific journal articles, and statistical data from several leading websites, this paper will describe the power relations and internet data in several countries and about the achievements of world information technology companies. The findings of this paper show that only three entities (two companies and one country) controlled the Internet (temporarily) until 2019: Google, Facebook, and China. This power makes every country in the world try to build domestic capabilities to control the internet, at least for local consumption as China did.